Wolf-Women and Phantom Ladies : Female Desire in 1940s US Culture - Dillon, Steven, 1960- (Book collections on Project MUSE., 2015)
Provides encyclopedic coverage of female sexuality in 1940s popular culture. Popular culture in the 1940s is organized as patriarchal theater. Men gaze upon, evaluate, and coerce women, who are obliged in their turn to put themselves on sexual display. In such a thoroughly patriarchal society, what happens to female sexual desire? Wolf-Women and Phantom Ladies unearths this female desire by conducting a panoramic survey of 1940s culture that analyzes popular novels, daytime radio serials, magazines and magazine fiction, marital textbooks, Hollywood and educational films, jungle comics, and popular music. In addition to popular works, Steven Dillon discusses many lesser-known texts and artists, including Ella Mae Morse, a key figure in the founding of Capitol Records, and Lisa Ben, creator of the first lesbian magazine in the United States.--Publisher website.